1954
DOI: 10.1038/icb.1954.12
|View full text |Cite
|
Sign up to set email alerts
|

OBSERVATIONS ON CARBOHYDRATE METABOLISM AND ALLOXAN DIABETES IN A MARSUPIAL (TRICHOSURUS VULPECULA)

Abstract: Bolliger and Whitten (1938) noticed that the urine of the common brushtail phalanger {Trichosurus vulpecula) usually contains reducing substances and gives a positive Bial reaction for pentose. These observations suggested an unusual carbohydrate metabolism in this marsupial and further studies of the urine and blood sugar of normal phalangers were, therefore, undertaken. In addition, alloxan was injected into a number of phalangers and the response to this diabetogenic compound compared with that obtained in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1963
1963
1997
1997

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Adams & Bolliger (1954) found that hypoglycaemia failed to appear after the injection of alloxan into the marsupial Trichosurus vulpécula and concluded that this represented a unique response to alloxan in mammals. However, in rabbits the presence or absence of the hyperglycaemic phase is a function of the length of the period of fasting before injection of alloxan (Griffiths, 1947).…”
Section: Discussionmentioning
confidence: 94%
“…Adams & Bolliger (1954) found that hypoglycaemia failed to appear after the injection of alloxan into the marsupial Trichosurus vulpécula and concluded that this represented a unique response to alloxan in mammals. However, in rabbits the presence or absence of the hyperglycaemic phase is a function of the length of the period of fasting before injection of alloxan (Griffiths, 1947).…”
Section: Discussionmentioning
confidence: 94%
“…By 60 days after hypophysectomy, N-acetylglucosamine concentrations had fallen to only slightly below the 4-day figures and were of the same order as those found in the other segments of the prostate of normal breeding animals ( (Griffiths, McIntosh & Leckie 1969 ;Renfree 1970). In contrast, the possum, a non-ruminant herbivore which has high blood glucose levels around 120 mg/100 g (Adams & Bolliger, 1954), has a similar prostatic glucose pattern to the tammar wallaby. Species differences in blood glucose levels cannot apparently be used to explain these differences in seminal and prostatic glucose.…”
Section: Discussionmentioning
confidence: 93%
“…. 459 .. 461 Non-ruminant herbivorous marsupials, like the Brush-tailed possum, Trichosurus vulpecula resemble their eutherian counterparts (Adams & Bolliger, 1954) in metabolic functions. They have, however, higher levels of glucose and lower levels of volatile fatty acids in their blood than ruminant species (Barker, 1961 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting this comes not only from studies of volatile fatty acid uptake but also from observations on the effects of pancreatic hormones such as insulin on blood sugar levels (White & Harrop, 1975). Diabetes induced by the injection of alloxan is tolerated better by non-ruminant than ruminant species (Adams & Bolliger, 1954;Grifflths, Mclntosh & Leckie, 1969). It seems likely that the hyperglycemia after the injection of alloxan depends on the level of glycogen in liver and that Trichosurus has a high liver glycogen content (Grifflths et al, 1969).…”
Section: Introductionmentioning
confidence: 99%